Imaging Biomarkers of Alzheimer Disease in Multiple Sclerosis. Issue 4 (8th February 2020) - Zeydan, Burcu; Lowe, Val J.; Reichard, Ross R.; Przybelski, Scott A.; Lesnick, Timothy G.; Schwarz, Christopher G.; Senjem, Matthew L.; Gunter, Jeffrey L.; Parisi, Joseph E.; Machulda, Mary M.; Vemuri, Prashanthi; Mielke, Michelle M.; et al.
Abstract : Objective: To investigate β‐amyloid and tau depositions using Pittsburgh compound B (PiB) positron emission tomography (PET) and AV1451 tau PET imaging in aging multiple sclerosis (MS) patients. Methods: Patients with MS (n = 16) and controls (n = 80) matched for age, sex, and APOE ε4 status from the population‐based Mayo Clinic Study of Aging who underwent PiB PET imaging were studied. Of these individuals, 12 patients with MS and 60 matching controls also underwent AV1451 tau PET. Cortical PiB and AV1451 standard uptake value ratios (SUVrs) from the entire cortex and previously determined Alzheimer disease (AD) signature regions in the same population were calculated for group comparisons and testing for associations with age. Results: AD signature PiB SUVr (odds ratio [OR] [95% confidence interval (CI)] = 0.52 [0.27–0.98], p = 0.044), total cortical PiB SUVr (OR [95% CI] = 0.52 [0.28–0.99], p = 0.048), and the frequency of abnormal PiB SUVrs (OR [95% CI] = 0.10 [0.01–0.90], p = 0.040) were lower in MS than controls. Although AD‐signature and total cortical AV1451 SUVrs were not different between the groups, the frequency of abnormal AV1451 SUVrs was higher (OR [95% CI] = 10.65 [1.10–103.35], p = 0.041) in MS than controls. The association of AD signature PiB SUVr with age was steeper in the controls compared to patients with MS (estimate [95% CI] = −0.14 [−0.023 to −0.006], p = 0.002). Similarly, the association of total cortical PiB SUVr with age was steeper in the controls compared to patients with MS (estimate [95% CI] = −0.13 [−0.021 to −0.005], p = 0.002). There was no difference in the association of AV1451 SUVr findings with age between the MS patients and controls. Interpretation: Although both β‐amyloid and tau are biomarkers of cognitive aging and AD, cortical β‐amyloid deposition was lower in MS than age‐matched controls, suggesting that some aspect of MS pathobiology retards the accumulation of β‐amyloid but not the accumulation of tau. ANN NEUROL 2020;87:556–567